2008
DOI: 10.1002/pssr.200802092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the local absorber layer thickness on the performance of ZnO nanorod solar cells

Abstract: The local absorber layer thickness (dlocal) of solar cells with extremely thin absorber was changed between 10 nm and 70 nm. As a model system, ZnO nanorod arrays (electron conductor) with fixed internal surface area coated with In2S3 (absorber) and impregnated with CuSCN (transparent hole conductor) were applied. The performance of the small area solar cells depended critically on dlocal. The highest short circuit current density was reached for the lowest dlocal. In contrast, the highest open circuit voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 10 publications
5
81
1
Order By: Relevance
“…In particular it was found that the In 2 S 3 thickness plays a crucial role for the cell performance. Although the light absorption could be increased with increasing In 2 S 3 thickness, a drastic drop in the short circuit current was observed for thicker films (9). For very thin films (<10nm) a strong reduction of the open circuit voltage Voc was found.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In particular it was found that the In 2 S 3 thickness plays a crucial role for the cell performance. Although the light absorption could be increased with increasing In 2 S 3 thickness, a drastic drop in the short circuit current was observed for thicker films (9). For very thin films (<10nm) a strong reduction of the open circuit voltage Voc was found.…”
Section: Introductionmentioning
confidence: 92%
“…For low cost solar cell designs, ZnO nanorod arrays that can be grown at low temperatures by either chemical bath deposition (8) or electrodeposition are particularly promising (7). Recently, we have shown 3.4% conversion efficiency for a nanorod ZnO/In 2 S 3 /CuSCN solar cell (9). In theory, with a surface enhancement by a factor of 10 (roughness factor) efficiencies of about 10%-15% can reasonably be achieved with an absorber thickness of only about 20-30 nm (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) In a typical quantum dot-based solar cell, the quantum dots are attached to a TiO 2 layer with a bifunctional linker molecule, usually mercaptopropionic acid. (3) Several different TiO 2 structures have been utilized in devices, including flat TiO 2 surfaces,(65) spherical nanoparticles,(3) nanowires, (66,67), and nanotubes. (8) Upon absorption of a photon, the photogenerated electron is extracted into the TiO 2 , while the photogenerated hole is extracted into either a hole-conducting polymer or an electrolyte.…”
Section: Ecs Transactions 33 (33) 3-16 (2011)mentioning
confidence: 99%
“…This is the category of nanocoax [21], nanocone [22,23], nanodome [24], nanopillar [25,26], nanorod [27][28][29][30][31], and nanowire [32][33][34][35][36][37] solar cells. Employing hydrogenated amorphous silicon (aSi:H) as light absorbing material, an efficiency of up to ~9% [18] has been reported for such nanostructured solar cells.…”
Section: Introductionmentioning
confidence: 99%